Hepatitis B and Hepatitis C Viral Infections in Patients with Chronic Lymphocytic Leukemia - Gerald Y Minuk; Betty Lerner; Spencer B Gibson; James B Johnston; Julia Uhanova; Anton Andonov; Jun Wu (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Whether chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections contribute to the pathogenesis and/or course of chronic lymphocytic leukemia is unclear.